Plasma membrane receptors of tissue macrophages: functions and role in pathology. Issue 5 (14th March 2020) - Gordon, Siamon; Plüddemann, Annette; Mukhopadhyay, Subhankar
Abstract: The cells of the mononuclear phagocyte system (MPS) constitute a dispersed organ, which is distributed throughout the body. Macrophages in different tissues display distinctive mosaic phenotypes as resident and recruited cells of embryonic and bone marrow origin, respectively. They help to maintain homeostasis during development and throughout adult life, yet contribute to the pathogenesis of many disease processes, including inflammation, innate and adaptive immunity, metabolic disorders, and cancer. Heterogeneous tissue macrophage populations display a wide variety of surface molecules to recognise and respond to host, microbial, and exogenous ligands in their environment; their receptors mediate the uptake and destruction of effete and dying host cells and pathogens, as well as contribute trophic and secretory functions within every organ in the body. Apart from local cellular interactions, macrophage surface molecules and products serve to mobilise and coordinate systemic humoral and cellular responses. Their use as antigen markers in pathogenesis and as potential drug targets has lagged in clinical pathology and human immunotherapy. In this review, we summarise the properties of selected surface molecules expressed on macrophages in different tissues and disease processes, to provide a functional basis for diagnosis, further research, and treatment. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.